2014
DOI: 10.4236/odem.2014.24009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Occupational Risk Factors for Healthcare Workers through Analysis of the Florida Workers’ Compensation Claims Database

Abstract: The purpose of this study is to evaluate occupational risk factors for nurses and CNAs by analyzing the Florida workers' compensation claims database. Risk factors for the cause of injury, nature of injury, body part injured, and demographic and lifestyle factors were evaluated for a sample of CNAs, nurses, and restaurant servers. The results identified falls, lifting, being struck, and pushing and pulling as major causes for injury among nurses and CNAs as compared to servers. Regarding the nature of injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Bullying is a similar concept and is described as repeated, health-harming mistreatment of one or more people by one or more perpetrators in the form of verbal abuse, threatening, humiliating or offensive behaviors or actions. Horizontal violence and bullying can negatively affect the work environment [ 54 ]. Studies by Secrest et al and Ejaz et al report that the work environment may be characterized by hostility, disrespect, and lack of control, as well as racially biased comments [ 10 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying is a similar concept and is described as repeated, health-harming mistreatment of one or more people by one or more perpetrators in the form of verbal abuse, threatening, humiliating or offensive behaviors or actions. Horizontal violence and bullying can negatively affect the work environment [ 54 ]. Studies by Secrest et al and Ejaz et al report that the work environment may be characterized by hostility, disrespect, and lack of control, as well as racially biased comments [ 10 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a review of worker’s compensation claims made of the Florida workers’ compensation claims database, weekly pay in dollars was analyzed and it was found that 88.2% of NAs received no pay while on leave, and the author proposed that the lack of pay was because most of them return to work within a few days of an injury for a continuous income and the fact that they view their roles as a career more than a job [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The growing prevalence of obesity is prohibitive of manual lifting as the National Institute of Occupational Safety and Health (NIOSH) guidelines recommend that the maximum recommended weight to be lifted by women in the 90th percentile of strength is 46 lbs. The cumulative weight lifted by a nurse in one typical 8-hour shift is equivalent to 1.8 tons, which surely exceeds NIOSH guidelines [9].…”
Section: A the Need For Safety Patient Handling Monitoringmentioning
confidence: 87%
“…In healthcare venues, nursing homes in particular, nursing assistants are on the front line to take care of patients. Their lower-back injury rate is more than seven times as high as the average for all workers (249 per 10,000 in healthcare compared to 34 per 10,000 [4]). Even in places where ceiling-mounted lifting equipment is installed, they are still required to handle the patient for bedside care, such as sliding the sling underneath the patient, scooping up the patient, putting on compression socks, etc.…”
Section: Introductionmentioning
confidence: 95%